Alternating-direction method for a mildly nonlinear elliptic equation with nonlocal integral conditions - Mifodijus Sapagovas; Olga Štikonienė (Nonlinear Analysis, 2011)
The present paper deals with a generalization of the alternating-direction implicit (ADI) method for the two-dimensional nonlinear Poisson equation in a rectangular domain with integral boundary condition in one coordinate direction. The analysis of results of computational experiments is presented.